A Delphi study to validate competency-based criteria to assess undergraduate midwifery students' competencies in the maternity ward. (October 2017) - Embo, M.; Helsloot, K.; Michels, N.; Valcke, M.
Abstract: Background: workplace learning plays a crucial role in midwifery education. Twelve midwifery schools in Flanders (Belgium) aimed to implement a standardised and evidence-based method to learn and assess competencies in practice. This study focuses on the validation of competency-based criteria to guide and assess undergraduate midwifery students' postnatal care competencies in the maternity ward. Method: an online Delphi study was carried out. During three consecutive sessions, experts from workplaces and schools were invited to score the assessment criteria as to their relevance and feasibility, and to comment on the content and their formulation. A descriptive quantitative analysis, and a qualitative thematic content analysis of the comments were carried out. A Mann-Whitney U-test was used to investigate differences between expert groups. Findings: eleven competencies and fifty-six assessment criteria were found appropriate to assess midwifery students' competencies in the maternity ward. Overall median scores were high and consensus was obtained for all criteria, except for one during the first round. Although all initial assessment criteria ( N =89) were scored as relevant, some of them appeared not feasible in practice. Little difference was found between the expert groups. Comments mainly included remarks about concreteness and measurability. Conclusion: this study resulted in validated criteria to assess postnatal care competencies in the maternity ward. Highlights: High-quality competency-based assessment requires clear assessment criteria. An online Delphi validation study helped collecting multidisciplinary expert opinions to ground the relevance and feasibility of a criteria list. Competency-based education reflects an entry-to-practice approach but experts worry about limited learning opportunities and the feasibility of criteria linked to autonomous performance. Recruitment from workplace professionals was more difficult than expected. Much remains to be done to improve the collaboration between practitioners and educators.